1999
DOI: 10.1093/dnares/6.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Genes for tRNAArg Located in the Upstream Region of the Shiga Toxin II Operon in Enterohemorrhagic Escherichia coli O157:H7

Abstract: We found two genes for tRNA(Arg) in the region upstream of genes for Shiga-like toxin type II (SLT-II) in Escherichia coli O157:H7. The two encoded forms of tRNA(Arg) recognize rare codons in E. coli K12 but these rare codons occur in the toxin genes at high frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Phages 21, ST64T and PS3 also carry one or both of these tRNA sequences in this location, but these have not been previously recognized as tRNA genes 22,25,26 (and GenBank accession AJ011579). Some other lambdoid phages, including 933W, 27 VT2-Sa 28 and FP27 29 carry isoleucine and arginine tRNA genes in this position, but the role of such tRNA genes is unknown in these cases (also see the text and Figure S3 of the Supplementary Material).…”
Section: Resultsmentioning
confidence: 99%
“…Phages 21, ST64T and PS3 also carry one or both of these tRNA sequences in this location, but these have not been previously recognized as tRNA genes 22,25,26 (and GenBank accession AJ011579). Some other lambdoid phages, including 933W, 27 VT2-Sa 28 and FP27 29 carry isoleucine and arginine tRNA genes in this position, but the role of such tRNA genes is unknown in these cases (also see the text and Figure S3 of the Supplementary Material).…”
Section: Resultsmentioning
confidence: 99%
“…The upstream regions flanking the 5Ј ends of the stx genes were reported to be conserved and continuous with phage sequences in a number of Shiga toxin-encoding bacteriophages (32,39,44). Genes for rare tRNAs are located in the neighborhood of the stx 2 genes, and it was suggested that these could play a role in effective expression of Stx2 (23,38). Correspondingly, the region located upstream from the stxA 2e gene was found to be conserved in 95 (86.4%) of the Stx2e strains investigated here, pointing to a common origin of the stx 2e genes in most of the strains.…”
Section: Discussionmentioning
confidence: 99%
“…AGA codons occur at high frequency in toxin-encoding genes of E. coli O157:H7 (31), and the cognate tRNA Arg (anticodon UCU) occurs in eight copies in this bacterium (as annotated in the genome NC_002695). Therefore, AGA_AGA is not shift prone in O157:H7 and is not avoided.…”
Section: Discussionmentioning
confidence: 99%